Next Pandemic? Yes, Please! How Covid-19 Pandemic Improved the Financial Condition of Polish Hospitals - Bem, Agnieszka; Prędkiewicz, Paweł; Siedlecki, Rafał; Ucieklak-Jeż, Paulina; Žukovskis, Jan (Journal of Finance and Financial Law, 2023)
The purpose of the article. The study aims to analyze how these special rules of financing during the pandemic affected the financial situation of hospitals in Poland. Methodology. We analyzed a sample of 86 Polish hospitals from 2019 to 2021. The financial condition is assessed based on financial ratios and the synthetic measure M1. We employ the Kruskall-Wallis test to confirm the differences between the values of financial ratios in the analyzed period. Results of the research. We confirm that due to the special rules and financing, combined with underperformance, the financial condition of Polish hospitals has slightly improved – especially in the case of operating margin, EAT to debt ratio and ROA.